Highly Active Thiol-functionalized SBA-15 Supported Palladium catalyst for Sonogashira and Suzuki-Miyaura Cross-coupling Reactions - Sarkar, Shaheen M.; Lutfor, M. R.; M. M., Yusoff (Royal Society of Chemistry, 2015)

(untitled)
Highly ordered mesoporous silica SBA-15 with pendent 3-mercaptopropyl groups has been prepared by condensation of surface silanols and (3-mercaptopropyl)trimethoxysilane. Treatment of the mercaptopropylated SBA-15 with (CH3CN)2PdCl2 gave a heterogeneous Pd-catalyst. The immobilized Pd-catalyst served as an efficient heterogeneous catalyst for Sonogashira and SuzukiÃ¢ÂÂMiyaura cross coupling reactions of aryl halides. Furthermore, the SBA-15 supported Pd-catalyst was recovered by a simple filtration from the reaction mixture and reused five times without significant loss of its catalytic activity.